Biomechanical measurement and analysis of colchicine-induced effects on cells by nanoindentation using an atomic force microscope. (23rd January 2018) - Liu, Lanjiao; Zhang, Wenxiao; Li, Li; Zhu, Xinyao; Liu, Jinyun; Wang, Xinyue; Song, Zhengxun; Xu, Hongmei; Wang, Zuobin
Abstract: Colchicine is a drug commonly used for the treatment of gout, however, patients may sometimes encounter side-effects induced by taking colchicine, such as nausea, vomiting, diarrhea and kidney failure. In this regard, it is imperative to investigate the mechanism effects of colchicine on biological cells. In this paper, we present a method for the detection of mechanical properties of nephrocytes (VERO cells), hepatocytes (HL-7702 cells) and hepatoma cells (SMCC-7721 cells) in culture by atomic force microscope (AFM) to analyze the 0.1 μg/mL colchicine-induced effects on the nanoscale for two, four and six hours. Compared to the corresponding control cells, the biomechanical properties of the VERO and SMCC-7721 cells changed significantly and the HL-7702 cells did not considerably change after the treatment when considering the same time period. Based on biomechanical property analyses, the colchicine solution made the VERO and SMCC-7721 cells harder. We conclude that it is possible to reduce the division rate of the VERO cells and inhibit the metastasis of the SMCC-7721 cells. The method described here can be applied to study biomechanics of many other types of cells with different drugs. Therefore, this work provides an accurate and rapid method for drug screening and mechanical analysis of cells in medical research.